Comparison of Fracture Risk by Using FRAX Score with and without DEXA Scan in Patients Presenting to Endocrine Unit - Wasti, KP; Bajracharya, MR; Karki, BB; Rijal, B; Bhattarai, M; Mall, D; Shrestha, PS; Nepal, R; Bisht, A; Shrestha, D; Sah, TP (Journal of Diabetes and Endocrinology Association of Nepal, 2024)
Background: To compare the fracture risk using FRAX with and without Bone Mineral Density (BMD) for predicting 10-year probability of major osteoporotic fracture (MOF) and hip fracture. Methods: This was a cross-sectional study conducted at Diabetes and Endocrinology unit, Bir hospital. In individuals aged 50 or above, fracture risk assessment was done initially with FRAX without BMD and then BMD assessment with DEXA scan was done and FRAX score with BMD was calculated. Patients with similar treatment recommendations on both FRAX with BMD and without BMD were placed in the concordance group whereas patients with different recommendations were placed in the discordant group. Results: A total of 82 patients were included in the study out of which 63(76.82%) patients showed concordance whereas 19(23.17%) showed discordance. The concordance was higher in patients with osteopenia with 37(90.24%) patients showing concordant recommendations whereas the concordance proportion was lower in patients with osteoporosis (63.42%). Among the various risk factors for osteoporotic fracture, only age showed statistically significant difference between the two groups with a higher age having a greater concordance. Conclusion: Fracture risk assessment with BMD and without BMD give similar fracture risk prediction only in patients with osteopenia. The concordance rate is higher in the osteopenia group as compared to the osteoporosis group. Further larger studies are required in Nepal to achieve a more statistically significant conclusion.